Challenges and opportunities for women working in the Jordanian tourism sector: Umm Sayhoun as a model - Abu Taweelih, Saleh Mohammad Ali (Journal of Humanities & Social Sciences, 2020)
The aim of the study is to unravel the challenges faced by women who work in the tourism sector, in the Umm Sayhoun area of the Petra District in southern Jordan, as well as, to identify the opportunities and resources, and the ways, by the help of which, they can reach them. The study used the Qualitative Feminist Approach/case study. And it benefited from the approach of the concept of social marginalization. And it used in-depth interview tools, non-participating observation, and focus groups. The results of the study discovered the most important challenges, namely: The inability to get involved into the formal economy, the racial discrimination, the seasonality of tourism, poor infrastructure, the weakness of skills and cognitive abilities. And the study shows the most prominent opportunities which are; Political empowerment, tourism product development, establishing local partnerships.